Characteristics and patterns of elective admissions to for-profit and not-for-profit hospitals in France in 2009 and 2010. (May 2015) - Weeks, William B.; Jardin, Marie; Paraponaris, Alain
Abstract: In the mid 2000s, in an effort to increase competition among hospitals in France – and thereby reduce hospital care costs – policymakers implemented a prospective payment system and created incentives to promote use of for-profit hospitals. But such policies might incentivize 'upcoding' to higher-reimbursed procedures or overuse of preference-sensitive elective procedures, either of which would offset anticipated cost savings. To explore either possibility, we examined the relative use and costs of admissions for ten common preference-sensitive elective surgical procedures to French not-for profit and for-profit sector hospitals in 2009 and 2010. For each admission type, we compared sector-specific hospitalization characteristics and mean per-admission reimbursement and sector-specific relative rates of lower- and higher-reimbursed procedures. We found that, despite having substantially fewer beds, for-profit hospitals captured a large portion of market for these procedures; further, for-profit admissions were shorter and less expensive, even after adjustment for patient demographics, hospital characteristics, and patterns of admission to different reimbursement categories. While French for-profit hospitals appear to provide more efficient care, we found coding inconsistencies across for-profit and not-for-profit hospitals that may suggest supplier-induced demand and upcoding in for-profit hospitals. Future work should examine sector-specific changes in relative use and billing practices of for elective surgeries, the degree to which these elective surgeries are justified in either sector, and whether outcomes differ according to sector used. Highlights: In France, for-profit hospitals capture much of the elective surgery market. In France, elective admissions to for-profit hospitals are shorter and less expensive. We found some evidence of supplier-induced demand in French for-profit hospitals. Future research should explore differences over time and outcomes across sectors.